The determinants of credit risk of 9 selected banks listed on Bursa Malaysia /Nur Afiqah Ridzuan - Ridzuan, Nur Afiqah (Faculty of Business and Management, 2019)
The aim of this study is to investigate the determinants of credit risk of 9 selected banks listed on Bursa Malaysia. 9 financial report of the banks listed on Bursa Malaysia were used to analyse for 14 years (2004 -2017). Pooled OLS Regression Model has been selected to investigate the relationship between return on assets, capital adequacy ratio, loan loss provisions, debt-to-equity ratio and bank size with non-performing loan as credit risk indicator. The finding is only loan loss provision is positively significant with credit risk whereas the capital adequacy ratio, debt-to-equity ratio and bank size are negative significant toward credit risk. On the other hand, only a variable positive insignificant relationship with credit risk which is return on assets.